Pharmacological Properties of CY 216 and of Its ACLM and BCLM Components in the Rabbit - Peyrou, V; Lormeau, J C; Caranobe, C; Gabaig, A M; Crepon, B; Salvin, S; Houin, G; Sié, P; Boneu, B (Thrombosis and Haemostasis, 1994)
This study compares some in vivo pharmacological properties of CY 216 and of its ACLM and BCLM components having a molecular weight above and below 5.4 kDa respectively. The anti-factor Xa/anti-thrombin ratio of these compounds determined in a rabbit plasma system were 2.5 and 1.2 for CY 216 and ACLM respectively while BCLM was devoid of anti-thrombin effect. After bolus intravenous injection, continuous infusion and subcutaneous administration, the clearances of anti-factor Xa activity generated by ACLM were, on the average, 2 and 1.5 times higher than those generated by BCLM and CY 216 respectively. The clearances of the anti-thrombin activity were comparable for CY 216 and ACLM, and higher than those of the antifactor Xa activity. The duration of the antithrombotic effect was investigated in the Wessler model after a single subcutaneous injection of 1000 anti-factor Xa units of one of the compounds. Using thromboplastin as thrombogenic stimulus, the most efficient agent was ACLM and the antithrombotic activity was essentially correlated to the circulating anti-thrombin activity. Using human serum as thrombogenic stimulus, ACLM and BCLM were more efficient than CY 216 and the antithrombotic activity was mainly correlated to the anti-factor Xa activity. The ability of the 3 compounds to inhibit venous thrombosis growth was compared: they were found equipotent and the antithrombotic effect was independent of the anti-thrombin activity. The pro-haemorrhagic properties were compared in the rabbit ear model. The activity of the 3 compounds were comparable and significantly less prohaemorrhagic than unfractionated heparin. These results suggest that the haemorrhagic potential of unfractionated heparin and of LMWH is independent of the anti-thrombin and anticoagulant activity, but related to the molecular weight. These observations indicate that factor Xa inhibition is a valuable target to prevent and to treat venous thrombosis and that the anti-factor Xa activity of a low molecular weight heparin (LMWH) largely contributes to its antithrombotic effect.